Clinical pathways for patients with giant cell arteritis during the COVID-19 pandemic: an international perspective. (January 2021) - Mackie, Sarah L; Brouwer, Elisabeth; Conway, Richard; van der Geest, Kornelis S M; Mehta, Puja; Mollan, Susan P; Neill, Lorna; Putman, Michael; Robinson, Philip C; Sattui, Sebastian E
Summary: Giant cell arteritis, a common primary systemic vasculitis affecting older people, presents acutely as a medical emergency and requires rapid specialist assessment and treatment to prevent irreversible vision loss. Disruption of the health-care system caused by the COVID-19 pandemic exposed weak points in clinical pathways for diagnosis and treatment of giant cell arteritis, but has also permitted innovative solutions. The essential roles played by all professionals, including general practitioners and surgeons, in treating these patients have become evident. Patients must also be involved in the reshaping of clinical services. As an international group of authors involved in the care of patients with giant cell arteritis, we reflect in this Viewpoint on rapid service adaptations during the first peak of COVID-19, evaluate challenges, and consider implications for the future.